The twenty-first century agricultural cooperative: Increasing the business credibility of smallholders - Badiane, Ousmane (2016)
The twenty-first century producer organization can be more than an advocate or marketing body. With modern information and communication technologies at their fingertips, such organizations can upgrade their skills as well as their operations, to offer a comprehensive set of services to their members. With such an intermediary working in their interest, the potential of African smallholders can be harnessed to feed the continent and fuel economic development.